Représenter l’engagement des volontaires français de la Waffen-SS : une analyse historique et narratologique de la bande dessinée « Berlin sera notre tombeau » - Bene, Krisztián (Acta Romanica Quinqueecclesiensis : La publication du Département d'Études Françaises et Francophones, Université de Pécs, 2025)
The comic book “Berlin Shall Be Our Grave” [Berlin sera notre tombeau] recounts the involvement of French volunteers in the Waffen-SS during the final days of the Battle of Berlin in 1945. Blending historical realism and dramatic narrative, the work offers a rare and controversial perspective on an episode long marginalized in French historiography. This article analyses the comic’s narrative structure, visual style, and ideological implications. By confronting the artwork with established historical research, the study explores how comics can shape collective memory and question traditional narratives of World War II.